Controlled Human Infection Studies: Proposals for guidance on how to design, develop and produce a challenge strain. (November 2021) - Bekeredjian-Ding, Isabelle; Trouvin, Jean-Hugues; Depraetere, Hilde; La, Carine; Suvarnapunya, Akamol E.; Bell, Alan; Mann, Alex; Meij, Pauline; Bethony, Jeffrey M.; Schellhaas, Linda; Nazziwa, Winfred Badanga; Karikari-Boateng, Eric; et al.
Abstract: There is an increasing need to establish quality principles for designing, developing and manufacturing challenge agents as currently these agents are classified differently by various jurisdictions. Indeed, considerations for challenge agent manufacturing vary between countries due to differences in regulatory oversight, the categorization of the challenge agent and incorporation into medicinal/vaccine development processes. To this end, a whitepaper on the guidance has been produced and disseminated for consultation to researchers, regulatory experts and regulatory or advisory bodies. This document is intended to discuss fundamental principles of selection, characterization, manufacture, quality control and storage of challenge agents for international reference. In the development phase, CMC documentation is needed for a candidate challenge agent, while standard operating procedure documentation is needed to monitor and control the manufacturing process, followed by use of qualified methods to test critical steps in the manufacturing process, or the final product itself. These activities are complementary: GMP rules, which intervene only at the time of the routine manufacturing of batches, do not contribute to the proper development and qualification of the candidate product. Some considerations regarding suitability of premises for challenge manufacturing was discussed in the presentation dedicated to "routine manufacturing". Highlights: Applicable local, national and regional guidelines on manufacture and use of challenge agents must be considered. As challenge agents are biological products, ICH guidelines should be followed. GMP contributes to the right execution of a process duly designed, developed and declared in the CMC documentation. Good documentation practice is critical, for adherence to procedures and regulatory requirements and process reconstruction. For challenge agents, a case-by-case approach should determine the extent of quality data (CMC and GMP) to be applied.